Pendayagunaan Dana Zakat Produktif Dalam Meningkatkan Kesejateraan Masyarakat Miskin Di Kabupaten Bungo. - Kurniadi, Sandy (Fakultas Syariah IAIN Kerinci, 2023)
This research aims to find out how the productive utilization model of zakat funds in improving the welfare of the poor in Bungo Regency. As well as to find out how the mustahik's economic condition after receiving productive zakat fund assistance in improving the welfare of the poor in Bungo Regency. This research uses a descriptive qualitative approach with the type of field research. that the productive zakat fund distributed by BAZNAS Bungo Regency in the Bungo Sejahtera program in the form of productive business capital assistance has not been fully effective, it can be seen that there are still mustahiqs who do not utilize productive business capital assistance properly, this happens due to the lack of knowledge mustahiqs have about the business they are running, lack of access to information and mustahiq knowledge and also the lack of monitoring from BAZNAS Bungo Regency.